Canopy and litter ant assemblages share similar climate - species density relationships - Weiser, M.; Sanders, N.; Agosti, D.; Anderson, A.; Ellison, A.; Fisher, B.; Gibb, H.; Gotelli, N.; Gove, Aaron; Gross, K.; Guenard, B.; Janda, M.; et al. (Royal Society Publishing, 2010)
Tropical forest canopies house most of the globe's diversity, yet little is known about global patterns and drivers of canopy diversity. Here, we present models of ant species density, using climate, abundance and habitat (i.e. canopy versus litter) as predictors. Ant species density is positively associated with temperature and precipitation, and negatively (or non-significantly) associated with two metrics of seasonality, precipitation seasonality and temperature range. Ant species density was significantly higher in canopy samples, but this difference disappeared once abundance was considered. Thus, apparent differences in species density between canopy and litter samples are probably owing to differences in abundance–diversity relationships, and not differences in climate–diversity relationships. Thus, it appears that canopy and litter ant assemblages share a common abundance–diversity relationship influenced by similar but not identical climatic drivers.